Stimulasi Hormon Oksitosin Pada Ibu Post Partum - Eka Ratnawati; Endang Susilowati (STIKES Ngesti Waluyo, 2025)
Postpartum mothers experience peak oxytocin hormone stimulation on the first to third day after giving birth. Oxytocin hormone facilitates the smooth release of breast milk from the breast. This research aimed to investigate the implementation of oxytocin stimulation and its preliminary effect on breastmilk secretion among postpartum mothers. This study was a quasi-experiment with a single-group pre-posttest design. Postpartum mothers (n=55) without contraindications to massage and willing to participate in the study received an oxytocin massage on the first postpartum day. Data was then analysed descriptively. The result showed that after oxytocin stimulation, status 1 on breast examination became 81,82% (increase 23,65%), milk release in the “spurting” category became 3,64% (increase 3,64%), the “dripping” category became 50,91% (increase 43,64%), the “dripping” category to 34,55% (decrease 21,81%), and “no milk flow” category to 10,91% (decrease 2.45%). Oxytocin massage increased breast milk production.